전자기록의 장기보존을 위한 이관절차모형에 관한 연구 - 천권주; Cheon, kwon-ju (기록학연구, 2007)
Traditionally, the concept of transfer is that physical records such as paper documents, videos, photos are made a delivery to Archives or Records centers on the basis of transfer guidelines. But, with the automation of records management environment and spreading new records creation and management applications, we can create records and manage them in the cyberspace. In these reasons, the existing transfer system is that we move filed records to Archives or Records centers by paper boxes, needs to be changed. Under the needing conditions of a new transfer paradigm, the fact that the revision of Records Act that include some provisions about electronic records management and transfer, is desirable and proper. Nevertheless, the electronic transfer provisions are too conceptional to apply records management practice, so we have to develop detailed methods and processes. In this context, this paper suggest that a electronic records transfer process model on the basis of international standard and foreign countries' cases. Doing transfer records is one of the records management courses to use valuable records in the future. So, both producer and archive have to transfer records itself and context information to long-term preservation repository according to the transfer guidelines. In the long run, transfer comes to be the conclusion that records are moved to archive by a formal transfer process with taking a proper records protection steps. To accomplish these purposes, I analyzed the 'OAIS Reference Model' and 'Producer-Archive Interface Methodology Abstract Standard-CCSDS Blue Book' which is made by CCSDS(Consultative committee for Space Data Systems). but from both the words of 'Reference Model' and 'Standard', we can understand that these standard are not suitable for applying business practice directly. To solve this problem, I also analyzed foreign countries' transfer cases. Through the analysis of theory and case, I suggest that an Electronic Records Transfer Process Model which is consist of five sub-process that are 'Ingest prepare ${→}$ Ingest ${→}$ Validation ${→}$ Preservation ${→}$ Archival storage' and each sub-process also have some transfer elements. Especially, to confirm the new process model's feasibility, after classifying two types - one is from Public Records center to Public Archive, the other is from Civil Records center to Public or Civil Archive - of Korean Transfer, I made the new Transfer Model applied to the two types of transfer cases. 기록관리 환경이 점차 자동화되고 효율성과 편리성을 보장해 주는 여러 가지 어플리케이션이 개발 보급됨으로써 기록은 사이버 공간에서도 생산, 관리될 수 있게 되었다. 이러한 상황에서 기록의 전자적 관리와 이관조항이 담긴 개정 법령이 시행된 점은 새로운 개념의 패러다임을 이행하려는 적절한 조치였다. 그러나 개정된 "공공기록물관리에관한법률"(이하 기록관리법)에서의 전자이관은 일반적인 개념만을 제시한 것으로 구체적인 실행방안과 절차가 조속히 마련되어야 한다. 기록을 이관한다는 것은 가치 있는 기록을 먼 훗날에도 이용하기 위해 수행하는 기록관리 과정의 일부이다. 따라서 기록을 생산한 생산자와 이관 받을 기관이 상호 협력하여 기록 자체와 그 맥락을 온전히 유지하면서 기준과 원칙에 따라 장기보존시설로 옮겨 보존해야 한다. 결국, 이관의 문제는 일정한 절차 속에서 있는 그대로의 기록을 신뢰할 수 있도록 아카이브로 옮겨서 장기보존 가능하도록 하는 것으로 귀결된다. 이를 위해, 모든 디지털 객체의 장기보존을 위한 표준인 OAIS 참조모형의 기능모델과 미항공우주국의 우주데이터 시스템 위원회(CCSDS : Consultative committee for Space Data Systems)에서 개발한 '생산자-아카이브 인터페이스 표준방법론(Producer-Archive Interface Methodology Abstract Standard-CCSDS Blue Book)'을 연구 분석하여 기록물관리기관간의 전자기록 이관을 위한 근거를 마련하였다. 또한 해외의 다양한 이관사례를 통해 표준과 실제의 갭을 최소화하고자 하였다. 결론적으로 '이관준비 ${→}$ 전송(접수) ${→}$ 검증 ${→}$ 보존처리 ${→}$ 저장소 저장'이라는 5단계와 단계별 하위절차로 구성되는 이관절차모형을 제안하였으며, 한국의 전자기록 이관구조를 '(특수)기록관에서 영구기록물관리기관으로의 이관'과 '민간부문에서 기록물관리기관으로의 이관'으로 구분하고 설계된 표준절차모형을 적용함으로써 실행 가능성을 입증해 보았다.